CD68+ cell count, early evaluation with PET and plasma TARC levels predict response in Hodgkin lymphoma - Cuccaro, Annarosa (John Wiley and Sons Inc., 2016)
Early response evaluation with [18F]fluordeoxyglucose (FDG) positron emission tomography after 2 cycles of chemotherapy (interim PET) has been indicated as the strongest predictor for outcome in classical Hodgkin lymphoma (HL). We studied the prognostic role of the number of tumor‐infiltrating CD68+ cells and of the plasma levels of TARC (thymus and activation‐regulated chemokine) in the context of interim PET in 102 patients with classical HL treated with Adriamycin, Bleomycin, Vinblastine, Dacarbazine (ABVD). After 2 ABVD cycles, interim PET according to Deauville criteria was negative (score 0–3) in 85 patients and positive (score 4–5) in 15 patients (2 patients technically not evaluable). TARC levels were elevated in 89% of patients at diagnosis, and decreased after 2 cycles in 82% of patients. Persistently elevated TARC levels in 18% of patients were significantly associated with a positive PET result (P = 0.007). Strong predictors for progression‐free survival (PFS) were a negative interim PET (85% vs. 28%, P < 0.0001) and CD68+ cell counts <5% (89% vs. 67%, P = 0.006), while TARC levels at diagnosis and at interim evaluation had no prognostic role. In multivariate analysis, interim PET, CD68+ cell counts and presence of B‐symptoms were independently associated with PFS. We conclude that although TARC levels are a biomarker for early response evaluation, they cannot substitute for interim PET as outcome predictor in HL. The evaluation of CD68 counts and B‐symptoms at diagnosis may help to identify low‐risk patients regardless positive interim PET.